RESEARCH OF STUDENTS' ATTITUDES TO THE VALUES OF PHYSICAL EDUCATION - Murodaliyeva Musharrafxona Tohirjon qizi (Galaxy International Interdisciplinary Research Journal, 2024)
The article presents the results of an anonymous survey conducted among students of the Kokan State Pedagogical Institute, which allows us to assess the real attitude of students from the faculties of primary and preschool education of the institute to the values of physical culture.